Reply to: The Use of the Newest Vital Sign in Children - Carol J. Howe; Gina Alexander; Christine Van Scoyoc; Jada L. Stevenson (SLACK Incorporated, 2019)
We thank Dr. Barry Weiss for his comments about our study on the use of the NVS in children. We certainly have consensus that the NVS is not an appropriate instrument to measure children's health literacy. However, we assert that it is vital for clinicians and researchers alike to assess the health literacy of all patients, including children-particularly those who are school-aged and making decisions about their nutrition independently of their parents. Adoption of healthy or unhealthy behaviors begins in childhood and continues into adulthood. Given the high rate of overweight and obesity among children in the United States, the importance of child health literacy cannot be overstated.